PEMBERDAYAAN KELUARGA: PENDERITA HYPERTENSI BERBASIS MANAJEMEN KESEHATAN DIRI EFEKTIF DALAM UPAYA MENCEGAH KOMPLIKASI DI KALURAHAN SINDUMARTANI, KECAMATAN NGEMPLAK, KABUPATEN SLEMAN. DAERAH ISTIMEWA YOGYAKARTA - Wittin Khairani; Sri Haryanti; Haryono, Haryono (JURNAL PENGABDIAN MANDIRI, 2024)
Hypertension if not controlled will cause complications. This condition is called "Silent Killer". The role of independence and empowerment of a family is very important to prevent complications for hypertension sufferers. The prevalence of hypertension in the Special Region of Yogyakarta is 11%. Nationally, hypertension cases in the Special Region of Yogyakarta rank 4th highest. Therefore, there is a need for empowerment activities that focus on empowering families by implementing effective self-health management in implementing a healthy lifestyle for family members who suffer from hypertension. The aim is to increase family independence in effective independent health management for hypertension sufferers. The methods and strategies used are in the form of Service Learning (SL) for families. As a result of this activity, families are able to independently manage nutrition, including: managing fruit, vegetables, grains/nuts, avoiding saturated fat foods, managing low-salt foods, maintaining ideal body weight, doing regular physical activity every day. for 30-60 minutes per day, don't consume alcohol, don't smoke, and it's important to control stress